B2O3 as a new sintering additive for perovskite-type SrTaO2N oxynitride ceramics. Issue 1 (2nd January 2022) - Masubuchi, Yuji; Miyamoto, Daiki; Higuchi, Mikio
ABSTRACT: The development of new sintering processes for ferroelectric perovskite-type oxynitrides is a crucial aspect of realizing practical applications of these materials. The present study examined the sintering of SrTaO2 N with B2 O3, a new additive. The addition of B2 O3 was found to significantly lower the sintering temperature. In addition, observations by transmission electron microscopy showed that the B2 O3 combined with SrO to form an amorphous structure that enhances the diffusion of elements during high-temperature sintering.